Stool immunoassay for identification of colorectal cancer and other significant gastrointestinal diseases risk groups - N. S. Sergeeva; Nina V. Marshutina; Ye. V. Zenkina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To carry out comparative analysis of diagnostic sensitivity of three immunochemical stool tests as a first step of laboratory algorithm to define high risk groups for colorectal cancer (CRC) and other clinically severe diseases of gastrointestinal tract (GIT). Material and methods. Content of hHb, hHb/ Hp and fTu M2-PK was investigated by solid-phase immunoenzyme tests in stool samples of 447 patients: 157 primary CRC cases, 121 stomach cancer (SC) patients, 64 ulcerative colitis (UC), 20 colonic polyps (CP) patients and 85 healthy donors. Following cut off levels were used: hHb - 2,0 µg/mL, hHb/Hp - 0,5 µg/ mL and fTu M2-PK - 4,0 U/mL. Results. The test systems for hHb and hHb/Hp in stool had high sensitivity, that was similar for CRC (89.5% of and of 87.9%, respectively) and UC (79.0% of and of 71.9%). The rate of exceeding upper thresholds for hHb and hHb/Hp in SC patients was 51.2 and 43.8%, respectively, and only 20% for CP patients. hHb and hHb/Hp markers had high specificity for healthy donors (95.3% of and of 97.6%, respectively). Close correlation between hHb and hHb/Hp indicates that these tests are interchangeable for CRC diagnostics. fTu M2-PK sensitivity was 79.2% for CRC, 68.3% - for UC, 51.2% - for SC and fTu M2-PK-specificity was 94.7% as compared to donors. If elevation of at least one marker in a pair (hHb and fTu M2-PK) will be considered as positivity of the test overall, the sensitivity of laboratory testing rises for CRC to 95.0%, for UC - to 83.6% and for SC - to 69.0% at specificity of 91.3%. Conclusions. Comparative analysis of three stool tests (hHb, hHb/Hp and fTu M2-PK) has shown that the optimal combination for detection of CRC risk groups includes detection of fecal hHb and fTu M2-PK. Increase of at least one marker in this pair may be due to the presence of severe gastrointestinal disease, including CRC, that allows to select patient for subsequent investigation of the digestive system. Key words: colorectal cancer, stomach cancer, ulcerative colitis, colonic polyps, fecal immunochemical test (FIT), hHb, hHb/Hp, fTu M2-PK.